Hierarchical Self‐Assembly of a Biomimetic Light‐Harvesting Antenna Based on DNA G‐Quadruplexes. Issue 7 (27th December 2012) - Sancho Oltra, Núria; Browne, Wesley R.; Roelfes, Gerard
Abstract A new modular approach to an artificial light‐harvesting antenna system is presented. The approach involves the hierarchical self‐assembly of porphyrin acceptor molecules to G‐quadruplexes tethered to coumarin donor moieties.